2017
DOI: 10.1063/1.4993486
|View full text |Cite
|
Sign up to set email alerts
|

Transition scenario and transition control of the flow over a semi-infinite square leading-edge plate

Abstract: In recent investigations of the flow over a square leading-edge flat plate, elliptic instability and transient growth of perturbations are proposed to explain the turbulent transition mechanism of the separating and reattaching flow reported in early experimental visualizations. An original transition scenario as well as a transition control method is presented by a detailed numerical study in this paper. The transient growth of perturbations in the separation bubble induces the primary instability that causes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 64 publications
2
9
0
Order By: Relevance
“…At lower A, we argue that this instability is not observed because the dynamics of the base flow is quite different (Chiarini et al 2022b), and much less time is available for the recirculation regions to interact with each other. An identical mechanism was later proposed by Huang et al (2017) to explain the onset of three-dimensionality in the flow over a blunt flat plate; see also Abdalla & Yang (2004). However, the flow past a rectangular cylinder is quite different from that past a blunt flat plate.…”
Section: Physical Mechanismsupporting
confidence: 51%
See 2 more Smart Citations
“…At lower A, we argue that this instability is not observed because the dynamics of the base flow is quite different (Chiarini et al 2022b), and much less time is available for the recirculation regions to interact with each other. An identical mechanism was later proposed by Huang et al (2017) to explain the onset of three-dimensionality in the flow over a blunt flat plate; see also Abdalla & Yang (2004). However, the flow past a rectangular cylinder is quite different from that past a blunt flat plate.…”
Section: Physical Mechanismsupporting
confidence: 51%
“…The same triggering mechanism is responsible for the transition to three-dimensionality in the flow over a blunt flat plate. In this case, however, the 3-D instability of the Kelvin-Helmholtz vortices shed from the LE is exactly subharmonic (Chaurasia & Thompson 2011;Huang et al 2017), since the base flow does not satisfy the spatio-temporal symmetry.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…They observed that the separated shear layer rolls up to form hairpin-like structures whose arrangement depends on the Reynolds number. A similar scenario is described by Chaurasia & Thompson (2011) and Huang et al (2017), who studied the three-dimensional instability of the flow over a long, sharp rectangular plate. They found that vortices shed from the LE are elliptically unstable to three-dimensional perturbations, and originate hairpin-like structures.…”
Section: Introductionmentioning
confidence: 64%
“…His research mainly focused on flow separation suppression, and did not focus on noise reduction. In addition, the primary instability of a squared leading-edge flat plate is reduced under a transition control method [25]. Therefore, to obtain better hydrodynamic noise suppression using leading-edge serrations, we must investigate the effect of flow control and noise reduction together.…”
Section: Introductionmentioning
confidence: 99%